2016
DOI: 10.1021/acschemneuro.6b00098
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Functional Alanine Positional Scanning of the α-Melanocyte Stimulating Hormone and NDP-Melanocyte Stimulating Hormone Demonstrates Differential Structure–Activity Relationships at the Mouse Melanocortin Receptors

Abstract: The melanocortin system has been implicated in the regulation of various physiological functions including melanogenesis, steroidogenesis, energy homeostasis, and feeding behavior. Five melanocortin receptors have been identified to date and belong to the family of G protein-coupled receptors (GPCR). Post-translational modification of the proopiomelanocortin (POMC) prohormone leads to the biosynthesis of the endogenous melanocortin agonists, including α-melanocyte stimulating hormone (α-MSH), β-MSH, γ-MSH, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Acetylation of the N-terminal has been demonstrated to increase the stability of α-MSH compared to des-acetylated α-MSH [44, 45]. The full length peptide possesses nonselective sub-nanomolar to nanomolar potencies at the MC1R, MC3R, MC4R, and MC5R [46, 47]. Alanine scans of α-MSH have also indicated the importance of the Met 4 , Phe 7 , Arg 8 , and Trp 9 positions for binding and functional activity at the mouse MC1R and rat MC3R [48, 49].…”
Section: Classic Peptide Melanocortin Ligandsmentioning
confidence: 99%
See 4 more Smart Citations
“…Acetylation of the N-terminal has been demonstrated to increase the stability of α-MSH compared to des-acetylated α-MSH [44, 45]. The full length peptide possesses nonselective sub-nanomolar to nanomolar potencies at the MC1R, MC3R, MC4R, and MC5R [46, 47]. Alanine scans of α-MSH have also indicated the importance of the Met 4 , Phe 7 , Arg 8 , and Trp 9 positions for binding and functional activity at the mouse MC1R and rat MC3R [48, 49].…”
Section: Classic Peptide Melanocortin Ligandsmentioning
confidence: 99%
“…Alanine scans of α-MSH have also indicated the importance of the Met 4 , Phe 7 , Arg 8 , and Trp 9 positions for binding and functional activity at the mouse MC1R and rat MC3R [48, 49]. A 2016 report examining the cloned mouse receptors indicated that in addition to positions Met 4 , Phe 7 , Arg 8 , and Trp 9 , the Glu 5 and His 6 positions also affect functional activity [47]. Expression of α-MSH in the central nervous system is predominantly in the hypothalamus [50].…”
Section: Classic Peptide Melanocortin Ligandsmentioning
confidence: 99%
See 3 more Smart Citations